A new Psammogammarus (Amphipoda: Eriopisidae) from anchialine pools on the Exuma Cays, Bahamas - Jaume, Damià; Iliffe, Thomas M.; Ham, Joris L. Van Der (Zootaxa, 2013)
Psammogammarus lucayensis sp. nov. is described from anchialine pools on Little Iguana Cay (Exuma Cays, Great Bahama Bank). It can be easily distinguished from the other 14 members of the genus by the combination of: 1) carpus of G2 longer than broad; 2) male G2 palm margin non-excavated, evenly convex and devoid of strong mid-palmar robust setae; 3) basis of P7 with subparallel margins; 4) armature arrangement of ventral margin of epimeral plates as 0–2–3; 5) posteroventral angle of epimeral plate III strongly produced; 6) protopod of U2 with distomedial angle armed with comb of 3–4 robust setae; 7) U3 endopod as long as exp1; and 8) telson with robust setae on tip. The generic diagnosis is amended in order to allow the precise characterization of members of Psammogammarus compared to other eriopisids.